Integrated dispatch for combined heat and power with thermal energy storage considering heat transfer delay. (1st April 2022) - Zhu, Mengshu; Li, Jinghua
Abstract: Installing thermal energy storage (TES) devices and utilizing the TES characteristic of heating networks are effective means of improving the flexibility of combined heat and power (CHP) systems. However, to truly take advantage of these, many factors such as the heat transfer (HT) processes, heat exchanger (HE) internal structure, HT area, mass flow rate, the HT delay are essential to be considered. These vital factors are not discussed in sufficient detail simultaneously and may lead to inaccurate modelling and underutilisation of thermal inertia. Thus, this paper investigates the HT process and thermal time-lag issues by analysing the structure and working characteristics of HE. A novel dispatch model considering HT delays is first established based on detailed HT processes. The developed model poses a strongly non-linear problem that is difficult to solve. Then, a decomposition-coordination method is proposed to deal with it. Furthermore, the sensitivity of different factors affecting HT delays is analysed so that the operator is able to configure parameters more clearly. Simulation results prove the necessity of considering the HT delay in CHP systems and the effectiveness of the proposed model. Further analyses also demonstrate that the proposed method offers higher accuracy than a solver and fitting method. Graphical abstract: Image 1 Highlights: The HT delay model is established to exploit the potential of thermal inertia thoroughly. HT processes and delays enable a more accurate analysis of CHP system operation. The TES effect of HT improves operational flexibility to consume renewable energy. The proposed algorithm can solve the nonlinear constraints introduced by HT processes.